2006
DOI: 10.2134/jeq2005.0140
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Kinetics and Equilibria of Organic Pesticides in Carbonatic Soils from South Florida

Abstract: A batch reactor was used to determine sorption kinetic parameters (k2, F, and K*) and the equilibrium sorption coefficient (K). The two-site nonequilibrium (TSNE) batch sorption kinetics model was used to calculate the kinetic parameters. Two probe organic pesticides, atrazine [2-chloro-4-ethylamino-6-isopropylamino-s-triazine] and diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] were studied using three carbonatic soils from South Florida (Chekika, Perrine, and Krome), one noncarbonatic soil from Iowa (Webste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 27 publications
5
52
1
1
Order By: Relevance
“…Indeed, the diuron sorption (k f ) values were highly and significantly (R 2 = 0.991; p b 0.001) correlated with the TOC content. While some workers report significant associations between the K f for diuron and TOC content (Liyanage et al, 2006;Cabrera et al, 2007;Cabrera et al, 2008a,b), other studies have found no such correlation (Oliver et al, 2005;Nkedi-Kizza et al, 2006).…”
Section: Sorption Studiesmentioning
confidence: 95%
“…Indeed, the diuron sorption (k f ) values were highly and significantly (R 2 = 0.991; p b 0.001) correlated with the TOC content. While some workers report significant associations between the K f for diuron and TOC content (Liyanage et al, 2006;Cabrera et al, 2007;Cabrera et al, 2008a,b), other studies have found no such correlation (Oliver et al, 2005;Nkedi-Kizza et al, 2006).…”
Section: Sorption Studiesmentioning
confidence: 95%
“…Two-site nonequilibrium model (TSNE) [21]. Among the nonequilibrium processes influencing sorption, the possible division of sorption sites into two types exists.…”
Section: Sorption Kinetic Modelsmentioning
confidence: 99%
“…Taking into account the scarce or null antecedents into the literature about the kinetic behavior of MSM in soils, especially in volcanic ash-derived soils, and the broad and increasing use of sulfonylurea herbicides in the world's agriculture, this work has been aimed at the application and discussion of two type of kinetic models: those that allow to establish principally kinetic parameters and modeling of sorption process, such as pseudo-first-and pseudosecond-order [18], and some ones frequently used to describe solute transport mechanisms of organic compounds on soils or different sorbents intended for remediation purposes [17,[19][20][21][22]. Such information is necessary for understanding and modeling leaching of target herbicides for preventing potential contamination of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2 is analogous to the work by Nkedi-Kizza et al (2006) with the difference that they implemented forward and backward reactions (k +/− ) for the mass transfer reaction in the two-site model, instead of using a transfer rate as in Eq. 2:…”
Section: Two-site Kinetic Modelmentioning
confidence: 99%
“…When applying the two-site model with forward and backward reactions, k − corresponds to ω (k + =k − • (1−f)/f, resulting from the kinetic sorption reaction at t=∞), c ∞ to c 0 ·ω/k, and the exponent k 2 /β to k used here (Nkedi-Kizza et al 2006). …”
Section: Two-site Kinetic Modelmentioning
confidence: 99%